Macrozoobenthos With Chemical and Physics factor in the Babura rivers Deli Serdang - Masdiana Sinambela; Mariaty Sipayung (Universitas Negeri Medan, 2015)
Research Title “Macrozoobenthos with physico-chemical factors on water and river Babura Deli Serdang”. The measured parameter is existence of macrozoobenthos That biotic factors and abiotic factors ie chemical and physical factors. Physical factors ie: temperature, turbidity, dan chemical factors ie factors: pH, Dissolved Oxygen (DO), dan BOD, COD, and fosfat. Macrozoobenthos were taken using a Surber net in Mei 2015, there are 2 station. Where with number of macrozoobenthos in the river Babura 12 individu ie : 1 sp in station 1 ie Melanoides sp and 4 sp in station 2 ( 12 individu) ie Melanoides sp 2 individu, Hetelimnius sp 1 individu, Elmidae 2 individu, Epicordulia sp 1 individu, Chironomus sp 4 Melanoides 2 sp, dan Dragonfly nymph 4 individu. Chemical and physical factors still life macrozoobenthos support. An ex post facto research initials, it can use as baseline. Keywords: existence, macrozoobenthos, factor physic, chemistry